ANALISIS DISIPLIN KERJA PEGAWAI BAGIAN PEREKONOMIAN SEKRETARIAT KABUPATEN LAMPUNG TIMUR - Epi Parela (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2010)
Discipline is a form of mental attitude in human beings, with consciousness will carry out andperform the applicable rules and foster good discipline in the government apparatus and in a person.There are several factors that influence such as leadership style and work discipline.From the results of quantitative analysis of research data obtained that the disciplineBetween Leadership Style with employees working at the Secretariat of the Economic Section ofEast Lampung regency has a positive relationship, and have the closeness of the relationship tiggi.